Pengaruh Beban Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada CV Nusantara Cipta Pratama: The Effect of Workload and Work Stress on Employee Performance at CV Nusantara Cipta Pratama - Muhammad Alifiandra Arrauf Firman; Mohammad Amas Lahat; Dani Chandra Utama (CV Warnak Johanna Nusantara, 2025)
This study aims to analyze the Effect of Workload (X1) and Work Stress (X2) on Employee Performance (Y) at CV Nusantara Cipta Pratama, Tangerang City. Data were collected using a questionnaire involving 30 employees at the head office of CV Nusantara Cipta Pratama. The results of the analysis using IBM SPSS V.26 software showed that Workload (X1) had a positive and significant effect on Employee Performance (Y) with a t-count of 10.428> t-table 2.052 and a significance level of 0.000 <0.05. On the other hand, Work Stress (X2) did not have a positive and significant effect on Employee Performance (Y) where the t-count value was -1.295> 2.052 and a significance level of 0.206> 0.05. Simultaneously, the results of the F Test show that Workload (X1) and Job Stress (X2) have a positive and significant effect on Employee Performance (Y) where the f-value is 55.862> f-table 3.354 and the significance level is 0.000 <0.05. This study concludes that Workload and Job Stress have a positive and significant effect simultaneously on Employee Performance at CV Nusantara Cipta Pratama, Tangerang City.